PECULIARITIES AND PROBLEMS OF FORMATION OF MECHANISM OF ECONOMIC SECURITY PROVISION OF HIGHER EDUCATION - Nikolay Plotnikov (Вестник Северо-Кавказского федерального университета)
In article questions of formation of the mechanism ofensuring the economic security of higher education, discussed its features in comparison with the mechanism of economic security. The author defines the role of the mechanism of ensuring the economic security of higher education, a comparative analysis of the principles of formation of mechanisms of economic security and economic security of higher education.